Analysis and study on biomarkers of local muscle fatigue caused by repetitive lifting task - Siwu Zhong; Ning Jia; Ying Qu; Xueyan Zhang; Qing Xu; Yan Yang; Zhi Wang; Zhongxu Wang (BMC Musculoskeletal Disorders)
Abstract Background Work-related musculoskeletal disorders (WMSDs) show a rapid growth trend. It has brought a huge economic burden to the society and become a serious occupational health problem that needs to be solved urgently. This study aimed to analyze the local muscle response under continuous ergonomic load, screen sensitive fatigue-related biomarkers and provide data support for the early prevention of local muscle damage and the exploration of early warning indicators. Methods Thirteen male college student volunteers were recruited to perform simulated repetitive manual lifting tasks in the laboratory. The lifting task was designed for 4 periods which lasted for 12 min in each, and then paused for 3 min for sampling. Local muscle fatigue is assesed by the Rating of perceived exertion (RPE) and the Joint analysis of sEMG spectrum and amplitude (JASA). Elbow venous blood was collected and 14 kinds of biomarkers were analyzed, which included Metabolic markers Ammonia (AMM), Lactic acid (LAC), Creatine kinase (CK), Lactate dehydrogenase (LDH), Cartilage oligomeric matrix protein (COMP), C-telopeptide of collagen I and II (CTX-I, CTX-II) and Calcium ion (Ca2+); Oxidative stress marker Glutathione (GSH); Inflammatory markers C-reaction protein (CRP), Prostaglandin E2 (PG-E2), Interleukin-6 (IL-6) and Tumor necrosis factor α (TNF-α); Pain marker Neuropeptide Y (NPY). Repeated measures analysis of variance (Repeated ANOVA), linear regression analysis, t-test and spearman correlation analysis were used to analyze the data. Results Both subjective and objective fatigue appeared at the same period. Serum AMM, LAC, CK, LDH, COMP, CTX-II, Ca2+ and NPY after fatigue were significantly higher than those before fatigue (p < 0.05). There was a certain degree of correlation between the markers with statistical differences before and after fatigue. Conclusions Metabolic markers (serum AMM, LAC, CK, LDH, COMP, CTX-II, Ca2+) and pain markers (serum NPY) can reflect local muscle fatigue to a certain extent in repetitive manual lifting tasks. It is necessary to further expand the research on fatigue-related biomarkers in different types of subjects and jobs in the future.